To Survive at School with Diabetes - Nowakowska, Halina; Lewartowska-Zychowicz, Małgorzata (INSTED: Interdisciplinary Studies in Education & Society, 2018)
During the last decades of the 20th century diabetes type 1 was recognised in younger and younger members of European population and today the highest incidence rate is observed between the 10th and 14th year of life. It is estimated that all over the world there are about 440 thousand children under 15 with a recognised diabetes type 1. Diabetes type 1, as a chronic illness, is a significantly difficult experience for a child, because it remarkably changes their lifestyle almost in all areas: functioning at home, at school, in relations with peers, as well as in the scope of pursuing passions and interests. Diabetes therapy must be carried out non-stop, through night and day. The key elements of treating that illness are numerously performed measurements during the day and night (from eight to 12 times) and recording the level of glycaemia in blood. The subject of our interest are the social school experiences (and to be more exact - the experience interpretations) of pupils suffering from diabetes. The method of "pure" netnography was used. The research material used in this study comes from the analysis of posts placed on the internet forum for diabetes patients - www.mojacukrzyca.org.pl. The reading of the posts of pupils touched by diabetes type 1 indicates their diverse experiences connected with daily functioning on the school territory and relations with peers. Those experiences are extremely different, from the ones full of empathy and acceptance from teachers' and peers' side to the hostile ones, characterised by negative emotions, e.g. jealousy.